Children’s mental health need in Ontario: measurement, variations in unmet need and the alignment between children’s mental health service expenditures and need - Duncan, Laura (My University, 2020)
This thesis draws on the 2014 Ontario Child Health Study (2014 OCHS) to address four contemporary and policy-relevant issues associated with measuring child and adolescent mental health need and children’s mental health service use in the general population. The first and second papers focus on the development and evaluation of instruments to measure child mental disorder. The first paper develops a simple, brief symptom checklist used to measure child mental disorder conceptualized as a dimensional phenomenon, a core concept in the 2014 OCHS. The second focuses on a briefer version of this checklist to measure child mental disorder dimensionally in general and clinical populations for the purposes of assessing and monitoring children’s mental health need. The third and fourth papers use these measures as the basis for assessing children’s mental health need in evaluations of policy-relevant health service questions. The third paper focuses on a substantive question about area-level variation in children’s unmet need for mental health services using 2014 OCHS data linked to government administrative data and 2016 Census data. The fourth paper estimates the extent to which child mental health service expenditures in 2014-15 were allocated according to children’s mental health need. Together, these papers respond to the need for simple, brief, self-report measures of child and adolescent mental disorders and show how these types of measures, in combination with administrative government data sources can advance our knowledge about policy and funding decisions in children’s mental health services research in Ontario.
Keywords: Children's mental health; Measurement; Reliability; Validity; Unmet need; Service use